ANALISIS PERSEPSI APARATUR SIPIL NEGARA TERHADAP PEMAHAMAN REFORMASI BIROKRASI UNTUK MENDUKUNG OPTIMALISASI KINERJA - Afriyana, Affan (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2022)
In realizing good governance and clean government in the era of bureaucratic reform, the State Civil Apparatus (ASN) has pledged the construction of integrity zones towards free areas from corruption and clean and serving bureaucratic areas. This not only affects the character of employees but on the performance of an institution or institution as a whole. The purpose of this study is to describe the understanding of bureaucratic reform reviewed from the integrity zone component as a benchmark to support the performance of employees of the State Civil Apparatus (ASN) of the Central Bureau of Statistics in Subang West Java Province. This research method uses qualitative descriptive methods. The results of this study showed that the strengthening of the character of ASN integrated in the integrity zone in change management is 81.48%, structuring of implementation is 81.48%, structuring the human resource management system is 80.78%, strengthening supervision is 78.24%, strengthening performance accountability is 79.94% and improving the quality of public services is 83.33%. Thus the understanding of the integrity zone in the State Civil Apparatus in the l Bureau of Statistics (BPS) in Subang is good category. So that it can have implications for the internalizationand character building of the State Civil Administration (ASN) optimally.